High-efficiency and air-stable P3HT-based polymer solar cells with a new non-fullerene acceptor - Sarah Holliday (Nature Portfolio, 2016)
In organic photovoltaics, the best performing devices usually involve low-bandgap polymers whose limited solubility and stability constrain the scalability of organic solar cells. Here, Holliday et al. develop a new acceptor and pair it with canonical P3HT to obtain 6.4% efficient and stable devices.